FurC (PerR) from Anabaena sp. PCC7120: a versatile transcriptional regulator engaged in the regulatory network of heterocyst development and nitrogen fixation. (28th May 2021) - Sarasa‐Buisan, Cristina; Guio, Jorge; Broset, Esther; Peleato, M. Luisa; Fillat, María F.; Sevilla, Emma
Summary: FurC (PerR) from Anabaena sp. PCC7120 was previously described as a key transcriptional regulator involved in setting off the oxidative stress response. In the last years, the cross‐talk between oxidative stress, iron homeostasis and nitrogen metabolism is becoming more and more evident. In this work, the transcriptome of a furC ‐overexpressing strain was compared with that of a wild‐type strain under both standard and nitrogen‐deficiency conditions. The results showed that the overexpression of furC deregulates genes involved in several categories standing out photosynthesis, iron transport and nitrogen metabolism. The novel FurC‐direct targets included some regulatory elements that control heterocyst development ( hetZ and asr1734 ), genes directly involved in the heterocyst envelope formation ( devBCA and hepC ) and genes which participate in the nitrogen fixation process ( nifHDK and nifH2, rbrA rubrerythrin and xisHI excisionase). Likewise, furC overexpression notably impacts the mRNA levels of patA encoding a key protein in the heterocyst pattern formation. The relevance of FurC in these processes is bringing out by the fact that the overexpression of furC impairs heterocyst development and cell growth under nitrogen step‐down conditions. In summary, this work reveals a new player in the complex regulatory network of heterocyst formation and nitrogen fixation.